12 dekabr' 1937, den' vyborov v Verchovnyj Sovet SSSR. Vse na vybory v Verchonyj Sovet SSSR! - Livanova, V., (1937)
'12 of Decembre 1937, election day for the Supreme Council of the SSSR. Vote all for the Supreme Council of the SSSR'.